Interplay of prior knowledge, self‐regulation and motivation in complex multimedia learning environments. (16th October 2015) - Song, H.S.; Kalet, A.L.; Plass, J.L.
Abstract: This study examined the direct and indirect effects of medical clerkship students' prior knowledge, self‐regulation and motivation on learning performance in complex multimedia learning environments. The data from 386 medical clerkship students from six medical schools were analysed using structural equation modeling. The structural model revealed that medical students' prior knowledge directly positively affected their learning outcome, self‐efficacy and performance approach goal orientation. The learners' self‐regulation had a significant positive direct effect on learning outcome. The learners' mastery goal orientation directly affected their learning outcome. Interestingly, inconsistent with our hypothesis, the learners' performance approach goal orientation showed a significant negative direct effect on learning outcome, and performance avoidance goal orientation had a significant positive effect on learning outcome. These findings help develop a more comprehensive understanding of the role of individual characteristics on learning performance of complex tasks in multimedia learning environments.